Analysis of peri-implant bone tissue between hydrophilic and rough implant surfaces in spontaneously hypertensive rats treated with losartan - Jaqueline Silva dos SANTOS; Gabriel MULINARI-SANTOS; Fábio Roberto DE SOUZA BATISTA; Pedro Henrique Silva GOMES-FERREIRA; Letícia Pitol PALIN; Cristina ANTONIALI; Roberta OKAMOTO (University of São Paulo, 2024)
Abstract Hypertensive individuals present alterations in their calcium metabolism that consequently decrease the concentration of this mineral in the bone tissue. Objectives to evaluate the morphological and functional characteristics of the peri-implant bone tissue that was formed during the healing process by the placement implants using two different surface treatments: hydrophilic Acqua™ (ACQ) and rough NeoPoros™ (NEO), in spontaneously hypertensive (SHR) and normotensive rats (Wistar) whether or not treated with losartan. Methodology In total, 96 male rats (48 Wistar and 48 SHR) were divided into eight subgroups: absolute control rough (COA NEO), absolute control hydrophilic (COA ACQ), losartan control rough (COL NEO), losartan control hydrophilic (COL ACQ), SHR absolute rough (SHR NEO), SHR absolute hydrophilic (SHR ACQ), SHR losartan rough (SHRL NEO), and SHR losartan hydrophilic (SHRL ACQ). The rats medicated with losartan received daily doses of the medication. NeoPoros™ and Acqua™ implants were installed in the tibiae of the rats. After 14 and 42 days of the surgery, the fluorochromes calcein and alizarin were injected in the rats. The animals were euthanized 67 days after treatment. The collected samples were analyzed by immunohistochemistry, biomechanics, microcomputerized tomography, and laser confocal scanning microscopy analysis. Results The osteocalcin (OC) and vascular endothelium growth factor (VEGF) proteins had moderate expression in the SHRL ACQ subgroup. The same subgroup also had the highest implant removal torque. Regarding microarchitectural characteristics, a greater number of trabeculae was noted in the control animals that were treated with losartan. In the bone mineralization activity, it was observed that the Acqua™ surface triggered higher values of MAR (mineral apposition rate) in the COA, COL, and SHRL groups (p<0.05). Conclusion the two implant surface types showed similar responses regarding the characteristics of the peri-implant bone tissue, even though the ACQ surface seems to improve the early stages of osseointegration.